Vitamin B Mitigates Thoracic Aortic Dilation in Marfan Syndrome Mice by Restoring the Canonical TGF-β Pathway - Tzu-Heng Huang (MDPI AG, 2021)
Thoracic aortic aneurysm (TAA) formation is a multifactorial process that results in diverse clinical manifestations and drug responses. Identifying the critical factors and their functions in Marfan syndrome (MFS) pathogenesis is important for exploring personalized medicine for MFS. Methylenetetrahydrofolate reductase (MTHFR), methionine synthase (MTR), and methionine synthase reductase (MTRR) polymorphisms have been correlated with TAA severity in MFS patients. However, the detailed relationship between the folate-methionine cycle and MFS pathogenesis remains unclear. Fbn1C1039G/+ mice were reported to be a disease model of MFS. To study the role of the folate-methionine cycle in MFS, Fbn1C1039G/+ mice were treated orally with methionine or vitamin B mixture (VITB), including vitamins B6, B9, and B12, for 20 weeks. VITB reduced the heart rate and circumference of the ascending aorta in Fbn1C1039G/+ mice. Our data showed that the Mtr and Smad4 genes were suppressed in Fbn1C1039G/+ mice, while VITB treatment restored the expression of these genes to normal levels. Additionally, VITB restored canonical transforming-growth factor β (TGF-β) signaling and promoted Loxl1-mediated collagen maturation in aortic media. This study provides a potential method to attenuate the pathogenesis of MFS that may have a synergistic effect with drug treatments for MFS patients.